Self-Focusing Property of Partially Coherent Beam With Non-Uniform Correlation Structure in Non-Linear Media - Lu, Lu; Wang, Zhiqiang; Yu, Jiayi; Qiao, Chunhong; Lin, Rong; Cai, Yangjian (Frontiers in Physics, 2022)
Coherence in a light beam has the potential to serve as a degree of freedom for manipulating the beam. In this work, self-focusing property of a partially coherent beam with a non-uniform correlation structure propagating in a nonlinear medium is investigated. Analysis of the evolution of beam width reveals that the coherence structure plays a vital role in the self-focusing formation. A threshold condition for the coherence radius is proposed for the first time, and the relation of self-focusing length and initial coherence radius is studied numerically and analytically. It is shown that a feasible approach for manipulating of the self-focusing length by adjusting the initial coherence radius is achieved.